PENGARUH LAYANAN PENGUASAAN KONTEN TERHADAP KEPERCAYAAN DIRI ANAK TERISOLIR - Alfin Prasetya; Elni Yakub; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect of service control of the content of the students' self confidence isolated grade X SMAN 5 Pekanbaru academic year 2015/2016. This research was conducted in SMA Negeri 5 Pekanbaru from March 2016 to May 2016. The method used is a method of real-experimental with patterns pretest-posttest control group design. Research subjects in this study were students of class X SMAN 5 Pekanbaru isolated. Data collection instrument was a questionnaire using Likert scale. Data analysis technique used is the technique of statistical correlation. Based on the results of Wilcoxon test is apparently a difference confidence isolated students before and after the implementation of sociodramas of 26.6%. Furthermore, after the comparison between the experimental group and the control group by Mann-Whitney test results there are significant differences confidence isolated students in the experimental group with the confidence of students isolated students in the control group.Keywords: Service mastery of content, isolated student's confidence.